2020
DOI: 10.1177/2059513120928494
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of ferric iron on the systemic efficacy of nephrilin peptide in burn trauma

Abstract: Introduction: Nephrilin peptide is a designed inhibitor of Rictor complex (also known as mTORC2), an evolutionarily conserved assembly believed to modulate responses to cellular stress. We previously demonstrated the ability of nephrilin peptide to suppress neuroinflammation, loss of body mass, glycaemic control and kidney function in a rat scald model, as well as sepsis mortality in a mouse model. The present study explores the effect of nephrilin plus iron formulations on clinically relevant outcomes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Nephrilin's efficacy in reversing the systemic effects of sepsis and burn trauma [9][10][11] appears to involve pro-homeostatic modulation of the underlying immune dysfunction. In this study, we measured the distribution of nephrilin peptide across lung tissues after administration via subcutaneous bolus injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nephrilin's efficacy in reversing the systemic effects of sepsis and burn trauma [9][10][11] appears to involve pro-homeostatic modulation of the underlying immune dysfunction. In this study, we measured the distribution of nephrilin peptide across lung tissues after administration via subcutaneous bolus injection.…”
Section: Discussionmentioning
confidence: 99%
“…Severe burn trauma is associated with secondary systemic effects including hyper inflammation, hypercatabolism, sepsis, organ failure, loss of glycemic control, delayed wound healing, and cognitive deficits [3][4][5][6][7][8] . We have demonstrated the efficacy of nephrilin peptide in combating many of these pleiotropic effects in burn trauma as well as in several rodent models of metabolic and xenobiotic stress [9][10][11][12][13][14] . When nephrilin peptide is injected subcutaneously into rodents, its Protor sequence is believed to reduce oxidative stress in target tissues by modulation of Rac1 phosphorylation and, more speculatively, its IGFBP3 sequence may mediate homeostatic immunomodulatory functions in addition to its described transporter functions [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These serious and enduring complications can lead to substantial morbidity and mortality [ 4 - 9 ]. We previously demonstrated the efficacy of nephrilin peptide in combating many of the pleotropic effects of burns [ 10 - 12 ]. Nephrilin treatment following burn injury reverses epigenetic and signaling changes in kidney tissue that lead to the activation of Rac1, and lowers elevations in markers of systemic oxidative stress such as urinary 8-isoprostane and plasma OHDG.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrilin treatment following burn injury reverses epigenetic and signaling changes in kidney tissue that lead to the activation of Rac1, and lowers elevations in markers of systemic oxidative stress such as urinary 8-isoprostane and plasma OHDG. In a recent publication we describe the variables most reliably modulated by nephrilin in the rat scald model, these variables falling into in seven distinct efficacy categories [ 12 , 13 ]. In addition, an analysis of gene expression in the central nervous system after burn injury showed that nephrilin beneficially modulated the expression of genes associated with astrocytosis, oxidative stress and immunosuppression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%